The Effects Of The Social Network On The School Children In A Contemporary World - Mammadova, Arzu (ADA University, 2017)
In recent years, social network has intensively been developed and spread in almost all parts of the world. While growing it become very popular among teenagers and especially, school children already addicted to the usage of social network due to different reasons such as entertainment and studying purposes. However, S.M.Kana and Katharine M. Donato indicate that spending a lot of time online can have some negative consequences, including not only physical disorders like vision or spine issues, but other health problems are also inevitable leading to dangerous outcomes in terms of development process of still mentally weak children (2005, p.1139). The goal of this paper is to demonstrate the impact of the usage of social network on the mental health of secondary school children. The paper also contains some data which consists of 11-12 questionnaire surveys given to parents of school children. The results of this paper can be used to take measures either by parents or network usage administration to prevent students from being "infected". The anticipated outcome of this study is the detection of negative sides of social network usage particularly on the mental health. The findings may be useful in the medical area related to the mental development procedure of teenagers and school age children.